Marriage and Women's Subalternity in the Ecranisation of Layla Majnun’s Story - Ahmad Syafa'at Junaidi; Suma Riella Rusdiarti (Buletin Al-Turas, 2023)
Purpose This article aimed to explain the textual changes in adapting Layla Majnun's story to the film Layla Majnun (2021). In addition, this article questioned the textual ideology of both works con-cerning marriage and women's subalternity.